Natural gas measurement handbook - Gallagher, James E. (Gulf Pub., 2006)
This information-packed volume covers all aspects of natural gas measurement.
Keywords: Natural gas -- Measurement.; Gas-meters -- Handbooks, manuals, etc.; elektronické knihy; electronic books